2019
DOI: 10.17478/jegys.548350
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped-Problem Based Learning Model Integrated With LMS-Google Classroom for Senior High School Students

Abstract: The purpose of this study was to determine the effect of using the LMS-Google Classroom-based Flipped-Problem Based Learning Model (FPBLM) in the process of learning mathematics in high schools in Medan, North Sumatra, Indonesia. In this study also saw the interaction between the level of Prior Mathematics Ability (PMA) of students with the application of flipped-problem based learning models based on LMS-Google Classroom. PMA students consist of high, medium and low levels This research is quasi-experiment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
131
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 35 publications
7
131
0
14
Order By: Relevance
“…If the creativity of students increases, it will be easier for students to find their learning patterns that are suitable for maximum learning outcomes. Ramadhani et al (2019) also added that the application of computer-based media that is integrated with the system is also proven to be able to increase student motivation. Right motivation and creativity will highly support students' development, especially the development of special abilities, such as problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%
“…If the creativity of students increases, it will be easier for students to find their learning patterns that are suitable for maximum learning outcomes. Ramadhani et al (2019) also added that the application of computer-based media that is integrated with the system is also proven to be able to increase student motivation. Right motivation and creativity will highly support students' development, especially the development of special abilities, such as problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%
“…Related research that has been conducted by other researchers including Context and Problem Based Learning through integrated approaches can increase student confidence in solving problems in chemistry learning so that learning could be more efficient (Baran & Sozbilir, 2018), The Problem-Based Learning Model is proven effective in improving problem-solving skills compared to conventional learning models (Ramadhani, Umam, Abdurrahman & Syazali, 2019;Yulianti, 2018), the use of C-PBL increases communication skills, students' achievement, and students' interest in the material and skills in utilizing time effectively (Williams & Mckenzie, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Through this process, students will develop as a whole. This means that student development does not only occur cognitively, but also effective and psychomotor aspects through an internal appreciation of the problem at hand (Huda et al, 2019;Ramadhani, 2018;Ramadhani, Umam, Abdurrahman, & Syazali, 2019). Some mathematics education experts have tried to study learning models that can shape student characters, and they found that problembased learning can be used as a tool to build students' characters (Macmath, Wallace, & Chi, 2009;Prabowo & Sidi, 2012;Soedjadi, 2000).…”
Section: Introductionmentioning
confidence: 99%